Do we need a Sharia Supervisory Board in every Islamic bank? - Asad Arsya Brilliant Fani; Dian Septi Purnamasari; Fajrin Intan Safitri (Universitas Darussalam Gontor, 2023)
Sharia compliance is crucial for Islamic Financial Institutions, so SSB an importantelement is the existence. The SSB is tasked with providing advice and suggestions tothe directors as well as supervising and making decisions, policies related to bankactivities so that they comply with sharia principles. The amount of remuneration inseveral banks is a problem in this research, so is it really necessary to have SSB in everybank, will the DSN not be enough? Remuneration can be allocated as an additionalfinancing fund for debtors. This paper examines the relationship between SSBeffectiveness, their remuneration, asset efficiency. Using a quantitative descriptivemethod, the Common Effect Model CEM as a model and form of dummy variable crosssection data. The results that can be drawn from this study are the SSB remuneration,the number of members of the SSB, the total number of meetings held and the size ofthe assets have a significant effect on financing. Even though the percentage ofremuneration in several banks is not reasonable, the role of SSB in each bank is stillvery much needed according to their roles and obligations.